SPECIAL INVENTORY PROBLEMS OF THE DEALER IN COLLECTORS' ITEMS. - Myers, John H. (The Accounting Review, 1953)
Abstract To dealer antiques, coins, stamps and other collectors' items have two special problems in inventory tasking and control. One is associated with identification of units and the other with determining cost. The problem of identification arises because the dealer seldom has two items alike. Consider, for example, stamps. To the untrained person two stamps may appear alike if they are of the same color, denomination, and design. To the more informed person, however, watermark in the paper, size of perforations, and minute details of design will distinguish one stamp from another. Moreover, if two stamps should be identical as to issue, they will still differ as to potential resale price and hence inventory value because of condition factors. Similar problems appear in other collectors' items. As a result the dealer in these items must identify each item carefully and probably will have but one of each. The problem of determining cost is a combination of the problems of retail method and of joint products. The usual way of acquiring antiques and other collectors' items is to buy a number of items at a time for a lump sum, as when a collection is bought from someone no longer interested in it or when a bunch of stuff comes from someone's attic.